Effectiveness of Learning Management and Communication on Learning Outcomes in Contextual Accounting Learning in Senior High Schools - Suyatmini, S; Rohmah, Wafrotur (Proceedings International Conference on Education Innovation and Social Science, 2024)
The aim of this research is to analyze and test the contribution of learning management and communication on student learning outcomes in contextual accounting learning. This is a correlational quantitative research. The research subjects were teachers and students of Senior High School of Surakarta, Central Java. The data were collected through observation, interview and questionnaires. The data analysis technique was multiple regression analysis. The research result showed that learning management and communication collectively made contribution to students learning outcomes of 48%. Meanwhile, partially learning management and communication made significant contribution to students learning outcomes of 39.7% and 28.8% respectively. This shows that learning outcomes are influenced by learning management and also effective teacher communication. The achievement of student learning outcomes depends on the teaching and learning process. Educators are not enough just to distribute various information about accounting to students, but students need to be equipped with the application of accounting materials through their experiences.